Gaya Kepemimpinan Kepala Desa dalam Meningkatkan Partisipasi Masyarakat pada Pembangunan Infrastruktur Drainase di Ampibabo - Riyatno Riyatno; La Samudia Dalili; Priyatna Prasetyawati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The purpose of the study was to determine the implementation of the Village Head's Leadership Style in Increasing Community Participation in Drainage Infrastructure Development in Ampibabo in Ampibabo Village, Ampibabo District, Parigi Moutong Regency. The type of research is descriptive with a qualitative approach; purposive informant determination technique; data collection through observation, interviews, documentation; and data analysis techniques using interactive models, namely data condensation, data presentation, and drawing conclusions. The results of the study showed that the Village Head's Leadership Style in Increasing Community Participation in Drainage Infrastructure Development in Ampibabo in Ampibabo Village, Ampibabo District, Parigi Moutong Regency has been implemented but has not been optimal. This can be seen in the instructive and consultative leadership styles, both of which have been implemented well. While the participation and delegation leadership styles have not been implemented as expected. The village head is expected to be able to encourage the community to participate so that drainage development runs quickly and smoothly for the progress of Ampibabo Village development. In addition, village officials (subordinates) can also increase their knowledge through formal and informal education so that the delegation given by the village head can be understood so that the task runs well.